2021
DOI: 10.1021/acs.jnatprod.0c01274
|View full text |Cite
|
Sign up to set email alerts
|

A Commercial Extract of Cyanotis arachnoidea Roots as a Source of Unusual Ecdysteroid Derivatives with Insect Hormone Receptor Binding Activity

Abstract: Ecdysteroids act as molting hormones in insects and as nonhormonal anabolic agents and adaptogens in mammals. A wide range of ecdysteroid-containing herbal extracts are available worldwide as food supplements. The aim of this work was to study such an extract as a possible industrial source of new bioactive ecdysteroids. A large-scale chromatographic isolation was performed from an extract of Cyanotis arachnoidea roots. Ten ecdysteroids ( 1 – 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
4
0
2
Order By: Relevance
“…The structure of the isolated compounds was elucidated based on their molecular formulas, which were obtained by high-resolution mass spectrometry (HRMS) and on detailed nuclear magnetic resonance (NMR) studies. A preliminary assessment of the NMR spectra revealed that the currently isolated compounds 2 – 4 shared structural similarities with 14β,15-dihydrocalonysterone ( 1 , C 27 H 42 O 7 ) that was recently reported by our group; 10 therefore, the structure elucidation is described in relation to this compound.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…The structure of the isolated compounds was elucidated based on their molecular formulas, which were obtained by high-resolution mass spectrometry (HRMS) and on detailed nuclear magnetic resonance (NMR) studies. A preliminary assessment of the NMR spectra revealed that the currently isolated compounds 2 – 4 shared structural similarities with 14β,15-dihydrocalonysterone ( 1 , C 27 H 42 O 7 ) that was recently reported by our group; 10 therefore, the structure elucidation is described in relation to this compound.…”
supporting
confidence: 55%
“…Furthermore, while the cytoprotective effect of 20E in mammals has been relatively well described, little is known about the pharmacology of minor ecdysteroids. Therefore, as a follow-up to our recent report, in this current study it was the aim to further evaluate the chemical value of the commercially available Cyanotis extract and the pharmacological value of the isolated ecdysteroids with regard to their potential cytoprotective effects on the BBB.…”
mentioning
confidence: 99%
See 3 more Smart Citations